From War Profits to Peace Dividends: The New Political Economy of Israel - Jonathan Nitzan; Shimshon Bichler (Capital & Class, 1996)
Since the late 1980s, Israel has been undergoing a profound transformation, characterized by reconciliation with its Arab neighbours and attempts to reintegrate into the regional economy, a transition from a militarized economy to open markets, and a decline of the collectivist ethos in favour of liberalism and free enterprise. This transition, we argue, is part of a world-wide shift from the 'depth' to 'breadth' of accumulation and the parallel globalization of ownership. In order to survive, the large Israeli corporations must substitute outward expansion for the old protectionism of a militarized economy, and give up domestic control in return for global alliances.
Keywords: 330; Arms; accumulation; acquisitions; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; crisis; debt; demographics; development; distribution; dual economy; elite; energy; finance; globalization; growth; imperialism; dis